2019
DOI: 10.2131/fts.6.225
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of 12-week continuous ingestion of D-allulose in borderline diabetes and type 2 diabetes

Abstract: D-allulose is a rare sugar with an almost zero calorie and is known to suppress postprandial hyperglycemia and fat mass accumulation. Although D-allulose has been reported to be safe in healthy subjects and overweight/obese adults, its safety in borderline diabetes and diabetes patients has not been evaluated. Therefore, we conducted an open trial aimed to investigate the long-term safety of D-allulose in borderline diabetes and type 2 diabetes. Subjects took 5 g of D-allulose with meals three times daily for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 34 publications
3
18
2
Order By: Relevance
“…Not only biliary enzyme activities but also liver deviance enzyme activities (AST and ALT) and the score of fatty liver improved with D-allulose intake (Table 10, 11). Similar results related to hepatic functions were reported in some previous studies Itoh et al, 2015;Tanaka et al, 2019). CDCA is a strong agonist for the Farnesoid X Receptor (FXR), which is a member of the nuclear receptors superfamily and regulates the metabolism of bile acid, cholesterol, lipoprotein, TG, and glucose.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Not only biliary enzyme activities but also liver deviance enzyme activities (AST and ALT) and the score of fatty liver improved with D-allulose intake (Table 10, 11). Similar results related to hepatic functions were reported in some previous studies Itoh et al, 2015;Tanaka et al, 2019). CDCA is a strong agonist for the Farnesoid X Receptor (FXR), which is a member of the nuclear receptors superfamily and regulates the metabolism of bile acid, cholesterol, lipoprotein, TG, and glucose.…”
Section: Discussionsupporting
confidence: 85%
“…Our results, however, demonstrated no significant changes related to renal functions (blood urea nitrogen, creatinine, uric acid, urine specific gravity, urinary microalbumin, and urine pH) by long-term and excessive D-allulose intake in both blood and urinary examinations. Other clinical studies have also reported similar results (Han et al, 2018;Hayashi et al, 2010;Tanaka et al, 2019). Results of other examinations, including physical, blood, and urine examinations, did not show clinical problems.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations